Intraosseous line insertion for the primary health care physician - Indiran Govender; Henry I. Okonta; Olukayode Adeleke; Selvandran Rangiah (South African Family Practice)
Early rapid access to the vascular system is essential in emergencies and is lifesaving. In this article, we will provide information on the common sites used, the equipment that is required, the indications and contraindications for intraosseous line insertion, how to correctly and safely do the procedure, medication that can be administered, post insertion line management and possible complications. This is a lifesaving procedure and primary healthcare physicians should acquire this skill.